2020
DOI: 10.1007/s10802-020-00654-3
|View full text |Cite
|
Sign up to set email alerts
|

Attentional Bias for Cues Signaling Punishment and Reward in Adolescents: Cross-Sectional and Prognostic Associations with Symptoms of Anxiety and Behavioral Disorders

Abstract: Heightened reward sensitivity has been proposed as a risk factor for developing behavioral disorders whereas heightened punishment sensitivity has been related to the development of anxiety disorders in youth. Combining a cross-sectional ( n = 696, mean age = 16.14) and prospective ( n = 598, mean age = 20.20) approach, this study tested the hypotheses that an attentional bias for punishing cues is involved in the development of anxiety disorders and an attentional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 55 publications
(110 reference statements)
0
5
0
Order By: Relevance
“…In line with [ 33 ] and [ 52 ], the proneness to attend to rewarding/punishing cues was indexed by the cue validity effect for cues signaling reward/punishment. The difference in reaction time between the cued and uncued location represents the cue validity effect.…”
Section: Methodsmentioning
confidence: 76%
See 2 more Smart Citations
“…In line with [ 33 ] and [ 52 ], the proneness to attend to rewarding/punishing cues was indexed by the cue validity effect for cues signaling reward/punishment. The difference in reaction time between the cued and uncued location represents the cue validity effect.…”
Section: Methodsmentioning
confidence: 76%
“…In order to take individual differences in reaction times into account when calculating the cue validity effects, we subtracted the individual’s mean reaction time on the practice trials on either cued or uncued trials from the corresponding mean scores. This subtraction reduces the correlation between the components (reaction time of cued trials and reaction time of uncued trials) of the cue validity effects and thereby improves the reliability of attentional proneness measures [ 33 ]. See Table 2 for the calculations of the cue validity effects and the reliability estimates.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies using the spatial orienting task have found no evidence for cross-sectional or ATTENTIONAL CAPTURE -REWARD AND PUNISHMENT 6 temporal associations between attentional bias for cues signaling reward or punishment and anxiety or behavioral problems (Kreuze et al, 2020(Kreuze et al, , 2022.…”
Section: Introductionmentioning
confidence: 90%
“…Similarly, this hypersensitivity to punishment has been linked to anxiety disorders (Bar-Haim et al, 2007). Other studies using the spatial orienting task have found no evidence for cross-sectional or temporal associations between attentional bias for cues signaling reward or punishment and anxiety or behavioral problems (Kreuze et al, 2020(Kreuze et al, , 2022.…”
Section: Introductionmentioning
confidence: 99%